PENGEMBANGAN EVALUASI DAN ALAT TES DALAM PEMBELAJARAN PAI BERBASIS IT DI MI ASY-SYAFI’IYYAH KOTA SINGKAWANG - Assadi, Assadi; Ubabuddin, Ubabuddin (ILJ: Islamic Learning Journal, 2023)
Learning Islamic Religious Education (PAI), tests and evaluation tools have an important role in measuring students' understanding of subject matter and their ability to apply religious values ??in everyday life. This research is a qualitative research, with data collection methods through observation, documentation and interviews. Data analysis using triangulation. Based on the use of these tests and evaluation tools, several conclusions can be drawn: 1. Measuring understanding: Tests and evaluation tools are used to measure the extent to which students understand the concepts and principles in PAI. Through tests, teachers can evaluate students' understanding of subject matter and identify areas that need strengthening or improvement. 2. Development of attitudes and values: Apart from understanding concepts, tests and evaluation tools can also be used to measure students' attitudes towards religion and moral values. Tests such as ethical assessments or case studies can help teachers evaluate the extent to which students apply religious values ??in everyday life. 3. Skills development: Tests and evaluation tools can also measure a student's ability to apply practical skills related to Islamic Religious Education, such as reading and understanding religious texts, attending religious services, or participating in religious activities.